Pengaruh Model Pembelajaran Project Based Learning Berbasis Podcast Terhadap Kreativitas Siswa Pada Mata Pelajaran IPS di SMPN 1 Jatinangor Kabupaten Sumedang - Salva Nissa Aulia Darwan; Muhamad Iqbal; Yeni Kurniawati (FKIP, Universitas Palangka Raya, 2024)
In the 21st century, education serves as more than a conduit for the mere transmission of knowledge; it evolves into a platform for nurturing diverse skill sets among students. Among these, creativity emerges as a pivotal asset in navigating the complexities of globalization. Nonetheless, the levels of student creativity often languish due to limited avenues for thorough exploration and expression of their ideas. To address this, innovative learning frameworks like the Project Based Learning (PBL) Model come into play, aiming to foster creativity among students. Seeks to examine the influence of employing a podcast-based PBL approach on student creativity. The study endeavors to compare the levels of creativity before and after implementing the podcast-based PBL model in experimental classes against control classes utilizing traditional recitation methods. Employing a pseudo-experimental approach with a non-equivalent control group design, the research engages two class cohorts: 8.A (control group, comprising 34 students) and 8.B (experimental group, comprising 34 students). Data collection methodologies encompass observation, documentation, and the distribution of student creativity questionnaires. Subsequent analysis is conducted utilizing SPSS software version 22.00 for Windows. The outcomes of the independent sample test indicate a significance value of 0.000, rejecting the null hypothesis (H0). Notably, the average creativity score of students in the experimental class registers at 36.53, compared to 34.29 in the control class, indicating a notable variance in student creativity levels between the two groups. In summary, the podcastbased project-based learning model proves effective in enhancing student creativity within social studies subjects, outperforming traditional recitation methods. The study showcases substantial enhancements across four dimensions of student creativity—fluency, flexibility, originality, and elaboration—with experimental classes yielding superior post-test grades compared to controls. This model fosters active student engagement, exploration, and experimentation, fostering a more significant boost in creativity compared to conventional recitation approaches